Numerical Study of Shell-And-Tube Heat Exchanger Performance with Various Baffle Spacing - Sugit Triyono; Teguh Hady Ariwibowo; Prima Dewi Permatasari (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2016)
Heat exchanger  is the instrument used to exchange the heat from one system to another that can be used as a heater or cooler. One of those types is shell-and-tube heat exchanger which is mostly used in many factories. Shell-and-tube heat exchanger consist of shell, which there are many tube inside it with baffles arranged along the shell-side. This study examines the effect of baffle spacing towards shell-and-tube heat exchanger performance which geometry have been specified first. This study used a simulation method developed by Heat Transfer Research Inc. (HTRI) to determine heat exchanger performances. Baffle spacing is set to various values: 30 mm, 60 mm, and 90 mm which one of each conditions also vary the mass flow rate to various number: 0.8333 kg/s, 0.1667 kg/s, and 0.25 kg/s. The simulation will generate outlet temperature of each fluid, overall heat transfer coefficient, and pressure drop. Baffle spacing 30 mm generates pressure drop 0.011 kPa while the increase of mass flow rate from 0.1660 kg/s to 0.250 kg/s also increase the value of pressure drop 0.030 kPa to 0.045 kPa. From those three variation of baffle spacing, baffle spacing 60 mm generates a stable value: 0.003 kPa, 0.007 kPa, and 0.015 kPa that is the optimum condition to gain the good performance of shell-and-tube heat exchanger.